Immunisation in a curative setting. Issue 6752 (22nd September 1990) - Kofoed, P E; Nielsen, B; Rahman, A K
Abstract : OBJECTIVE--To study the uptake of vaccination offered to women and children attending a curative health facility. DESIGN--Prospective survey over eight months of the uptake of vaccination offered to unimmunised women and children attending a diarrhoeal treatment centre as patients or attendants. SETTING--The International Centre for Diarrhoeal Disease Research, Dhaka, Bangladesh. SUBJECTS--An estimated 19, 349 unimmunised women aged 15 to 45 and 17, 372 children attending the centre for treatment or accompanying patients between 1 January and 31 August 1989. MAIN OUTCOME MEASURES--The number of women and children who were unimmunised or incompletely immunised was calculated and the percentage of this target population accepting vaccination was recorded. RESULTS--7530 (84.2%) Of 8944 eligible children and 7730 (40.4%) of 19, 138 eligible women were vaccinated. Of the children, 63.8% were boys, 75.9% were aged under 1 year, and 23.0% were aged 1 to 2 years. The estimated number of missed opportunities for vaccination was 716 among the children (8.0% of the target population) and 11, 408 among the women (59.6% of those eligible). CONCLUSION--It is possible to establish immunisation services at a health facility treating acutely ill patients.